Decode China's Economic Engagement in Africa: Evolving Policies, Investment and Trade Trends, and Implications - Yuhan Zhang; Shimelse Mekonnen (ZBW - Leibniz Information Centre for Economics, 2023)
This working paper systematically analyzes the dynamic commercial relationship between China and Africa. Utilizing Natural Language Processing and content analysis of meticulously collected policy documents, this study finds that the Belt and Road Initiative (BRI) and other proposals by President Xi have shaped the policy direction of China-Africa collaborations, highlighting areas like industrial evolution, infrastructure synergies, agricultural modernization, and sustainable development. By exploring historical economic data, this study also finds that the BRI has significantly influenced Chinese financial commitments to Africa, with investment benefiting 30 distinct African countries, spanning sectors beyond natural resources, and involving both state-owned and private entities. Trade data suggests emerging signs of diversification and reveals China's consistent trade surpluses with Africa, influenced by significant Chinese capital outflows. While Africa's emerging signs of diversification are encouraging, it needs to further diversify into manufacturing and services to avoid mirroring past trade patterns with the West. Our machine learning analysis anticipates China-Africa trade to surpass 300 billion by 2025-6. In light of evolving policies and economic trajectories, this study identifies burgeoning opportunities in sectors like e-commerce, fintech, and agritech, underlying the immense potential of China-Africa commercial ties. However, it is important to acknowledge that China-Africa commercial cooperation is not without challenges. Disparities in trade balances, concerns about debt sustainability, and local economic impacts have sometimes strained relations, which require continuing attention and further research.
Keywords: A1; A12; 330; Machine Learning; Economic Policy; China; Africa; Belt and Road Initiative (BRI); Investment; Trade; Commercial Opportunities